The The Feminism Perspective in the "Si Parasit Lajang" Novel by Ayu Utami: A Feminist Standpoint Theory Nancy C. M. Hartsock Studies - Nugroho, Azis; Suseno, Suseno; Prabaningrum, Dyah (Jurnal Sastra Indonesia, 2021)
Tujuan penelitian ini adalah untuk mengkaji bentuk-bentuk perspektif feminisme dalam novel Si Parasit Lajang karya Ayu Utami menggunakan kajian feminist standpoint theory Nancy C. M. Hartsock. Sumber data dalam penelitian ini adalah novel Si ParasitLajang karya Ayu Utami. Data dalam penelitian ini adalah data-data berupa kutipan yangterdapat dalam novel Si Parasit Lajang karya Ayu Utami. Teknik yang digunakan dalam penelitian ini mencakup dua hal, yakni teknik pengumpulan data dan Teknik analisis data. Teknik pengumpulan data yang digunakan adalah teknik baca dan teknik catat dengan menandai informasi-informasi penting yang berkaitan dengan pokok penelitian. Sedangkandalam menganalisis data, teknik yang digunakan yaitu teknik analisis deskriptif denganmendeskripsikan data-data berupa kutipan mengenai perspektif feminisme dalam novel Si Parasit Lajang karya Ayu Utami menggunakan kajian feminist standpoint theory Nancy C.M. Hartsock.. Hasil penelitian menunjukkan bahwa terdapat bentuk-bentuk perspektif feminisme yang ditemukan. Bentuk-bentuk perspektif feminisme, antara lain (1) standpoint(sudut pandang): standpoint tokoh ‘saya’ tentang simbol status dalam masyarakat, standpointtokoh ‘saya’ tentang pola hidup sederhana, standpoint tokoh ‘saya’ tentang kemewahan; (2)situated knowledge (pengetahuan tersituasi): situated knowledge tokoh ‘saya’ terhadap rezimmiliter pada masa pemerintahan Soeharto, situated knowledge tokoh ‘saya’ terhadap duniayang hierarki, situated knowledge tokoh ‘saya’ terhadap seksualitas, situated knowledgetokoh ‘saya’ terhadap perkawinan dan poligami; dan (3) sexual division of labour(pembagian pekerjaan berdasarkan jenis kelamin): eksploitasi wanita.Kata Kunci: perspektif feminisme; feminist standpoint theory Nancy C. M. Hartsock; novelSi Parasit Lajang karya Ayu Utami; standpoint; situated knowledge; sexual division of labour.Abstract: The purpose of this study is to examine the forms of feminism perspective in the Si Parasit Lajang novel by Ayu Utami using a feminist standpoint theory of Nancy C. M. Hartsock. The data source in this research is Ayu Utami's novel Si Parasit Lajang. The datain this study are data in the form of quotations contained in the novel Si Parasit Lajang by Ayu Utami. The techniques used in this study include two things, namely data collection techniques and data analysis techniques. The data collection techniques used were reading and note-taking techniques by marking important information related to the subject of the research. Meanwhile, in analyzing the data, the technique used is descriptive analysis technique by describing the data in the form of quotations regarding the the forms offeminism perspective in the Si Parasit Lajang novel by Ayu Utami using a feminist standpoint theory of Nancy C. The results show that there are form of feminism perspective found. The form of feminism perspective, there are (1) standpoint (point of view): the standpoint of the "me" character regarding status symbols in society, the standpoint of the "me" character about a simple lifestyle, the standpoint of the "me" character about luxury; (2) situated knowledge: situated knowledge of the 'me' figure towards the military regime during the Soeharto era, the situated knowledge of the 'me' figure towards the world that is hierarchical, the situated knowledge of the 'me' character towards sexuality, the situated knowledge of the 'me' figure against marriage and polygamy; and (3) sexual division of labor (division of work based on sex): exploitation of women.Keywords: feminism perspective; feminist standpoint theory Nancy C.M. Hartsock; the Si Parasit Lajang novel by Ayu Utami; standpoint; situated knowledge; sexual division of labor.